Measuring Teacher's Competency in Describing Student Activities in Learning with Problem Based Learning - Safi'i, Imam; Wahdini, Leli; Warpitasari, Reni (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2023)
Utilization of problem based learning models will be able to increase student activity in learning. Many researches on problem based learning (PBL) have been carried out, but research that explores teacher competence in describing student activities in learning with the PBL model has not been done much. The purpose of this study is to analyze the teacher's competence in explaining student activities in learning with a PBL. This study uses the matching method, namely by matching the learning activities that have been developed by the teachers with the PBL syntax, namely in the form of orienting students to problems, organizing students to learn, guiding investigations, presenting work, and evaluating problem solving. The source of the data in this study is the implementation plan for learning Indonesian which has been prepared by teachers of SMP, SMA, and SMK. The results showed that the average competence of teachers in describing aspects of student orientation to problems was 17.24, organizing students to learn 55.17, guiding investigations was 55.17, presenting the work of 62.07, and evaluating problem solving was 58, 62. The overall competency average is 49.7 (less competent). The results of this study can be used as a basis for measuring teacher competence.